An Investigation of Eldercare Practices in Thailand through Institutional Logics Lens - Phayungphong, Santhita (ABAC ODI JOURNAL Vision. Action. Outcome, 2020)
The purpose of this research is to unfold the compelling logics that shape collective norms and behaviors, and to collect empirical evidence on how the changing context of the Thai family structure is affecting the geriatric and long-term care industry in Thailand. This study employs the constructivist grounded theory method under the theoretical view of the institutional logics perspective. A purposeful selection of participants is identified by their involvement and expertise in the area of study. Data collection from intensive interviews and non-verbal observations are retrieved and analyzed according to participants’ experiences, perceptions, and perspectives. Through a comprehensive analysis, ranging from the beginning of the aging society phenomenon to the current development along with its rationale. This research revealed that, first, unlike other institutional theories, the institutional logics perspective is differentiated chiefly through the causal linkage of multiple derivations. Second, the two contrasting logics that emerged from the study were “individualism” and “communitarianism.” Third, the community logic can function as the central core for Thai eldercare to facilitate informal care, social care, family care, as well as self-care. One most common practice is to rearrange living environments according to “universal design” principles in order to empower the independence of Thai elderly. Should the idea be implemented on a wider scale, such as urban and landscape designs, this aging in place approach could provide a promising alternative to reconnecting and restoring the communal relationship among urban communities.